The Fate of L5–S1 With Low-Dose BMP-2 and Pelvic Fixation, With or Without Interbody Fusion, in Adult Deformity Surgery. Issue 11 (1st June 2015) - Annis, Prokopis; Brodke, Darrel S.; Spiker, William R.; Daubs, Michael D.; Lawrence, Brandon D.
<x xml:space="preserve">Abstract</x> Study Design. Retrospective comparative case series. Objective. Evaluate L5–S1 fusion rates when lower dose of bone morphogenic protein-2 (BMP-2) (average 3.2 mg) and pelvic fixation were used, with or without interbody fusion. Summary of Background Data. Pseudarthrosis at L5–S1 is one of the most common complications of long fusions to the sacrum in adult deformity surgery. Strategies for decreasing pseudarthrosis include interbody fusion, use of BMP-2 at the lumbosacral junction, and the use of sacropelvic fixation, individually or in combination. High-dose BMP-2 (20–40 mg) placed posterolaterally has shown comparable fusion rates with interbody fusion. Methods. Retrospective review of 61 consecutive patients with minimum 2-year follow-up at a single institution. All patients had an isolated posterior approach, 5 or more levels fused including L5–S1, use of pelvic fixation, and no prior L5–S1 procedures. The patients were divided in 2 groups for comparison on the basis of the use of an interbody cage/fusion at the L5–S1 level. Revision rates and implant-related complications were also reported. Results. The fusion rate at L5–S1 was 97% (59/61), with no difference between the interbody and no interbody fusion groups (97% vs. 96%, P = 1.0). There were no significant differences in the radiographical parameters or deformity correction between the groups. The mean amount of BMP-2 used in the interbody group was 4.1 mg (2–10), 2.5 mg (0–8) in the disc space, and 1.6 mg (0-4) in the interbody cage, whereas there was no difference in the amount of recombinant human bone morphogenic protein-2 placed posterolaterally between the 2 groups (interbody fusion = 1.6 vs. non–interbody fusion = 2.0 mg, P = 0.08) along with autograft and allograft. The overall revision rate for L5–S1 nonunion was 1.6%. Conclusion. The use of low dose of BMP-2 at the L5–S1 level in combination with sacropelvic fixation achieved satisfactory fusion rates in adult deformity surgery. No additional benefit was encountered by adding an interbody cage. Level of Evidence: 4